Optimizing Juvenile Assessment Performance, United States, 2003-2019 - Hamilton, Zachary ([Verlag nicht ermittelbar], 2021)
In nearly every state and in the vast majority of juvenile justice agencies, risk assessments are incorporated into diversion, case management, supervision, and placement practices. Despite two decades of use within the juvenile justice system, little research regarding the methods of risk assessment development is discussed or translated to the field and practitioners. Many of the contemporary tools used today are implemented off-the-shelf, meaning that tools were developed with a specific set of methods, selecting and weighting items used in the prediction of a specified sample of youth. What is not known is how the various designs, methods, and circumstances of tool development impact the predictive performance when adopted by a jurisdiction. This study seeks to provide input into this dilemma. Demographic information in this study includes age, race, and sex.